Russian Trade Unions: Transformation of the Relations Inside the Traditional Structure - Ирина Марковна Козина (Journal of Economic Sociology, 2010)
One of the most important consequences of the democratic changes in the trade unions is the acquisition of the considerable financial and organizational freedom by the primary organizations. At the same time the transformation of relations inside the trade unions’ structure is going on. One of the new features links to the change of the role and place of the primary organization. The main theoretical approach of the paper is that the autonomy of the primary organization is due to the different interests of the low level managers and trade unions’ structures of high level.  The author analyzes this hypothesis on the basis of the example of the trade unions’ decision on financial questions and the settlement of authoritative relations. Empirical data is used.